The pet in contemporary art - Pretorius, Elmarie (My University, 2011)
The purpose of this paper is to investigate the figure of the pet in contemporary art. I will argue that the pet offers rich potential for creative exploration that challenges the conventional binaries of self/other, human/animal, and tame/wild in a way that tries to speak of a different subjectivity. I take as a starting point that the pet is seen as not other enough and this explains its relative absence in contemporary visual art practice and discourse. Currently there is a lot of interest in the animal within this field, but the animal is usually cast as wild or untamed – all too often functioning as a signifier of difference from the human (through this difference, of course, we define what is human). For all that the pet is an animal it does not serve as a signifier in the same way. It straddles binaries/boundaries of human/animal and even self/other in a manner that is often interpreted as ‘uncomfortable’. I will argue that the widespread prejudice against pets is based on a very deep seated and problematic formulation of the wild, and if the binary opposition of the wild and the domestic is discarded (as the binary opposition of the human and the animal was/is) the pet is more than equal to the same theoretical, and consequently practical, burden as the wild animal. With special attention to the concept of becoming-animal, outlined by Deleuze and Guattari, I look at the artists Jo Ractliffe, Carolee Schneemann, and William Wegman whose pets play a pivotal role in the production of their artworks, and in some cases, the trajectory of their careers. I contend that within this cross-species relationship/experience/void/communication (or any other description one might hazard to apply) something happens, an event, something meaningful, worth consideration. The very nature of a cross-species phenomenological, libidinal relating is, for me, laden with creative possibility. I argue that the pet has the potential to open up a creative space within which important and topical issues, anxieties and subject fractures can be visually manifested
MA (Fine Art), Faculty of Humanities, University of the Witwatersrand, 2011
Keywords: pets; animals; art